The Impact Of Personal, Sociological And Institutional Influences On Relationship Commitment In Retail Banking - Bojei, Jamil; Che Wel, Che Aniza (Asian Academy of Management (AAM), 2003)
Previous research in the domain of relationship marketing has focused mainly on the antecedents of loyalty and commitment in the industrial market, distribution channel or consumer goods. This study however, models the antecedents of consumer's relationship commitment in the context of a retail banking service. The impact of the four key explanatory variables (personal influences, sociological influences, institutional influences, and trust) are examined. The results support the hypothesized model and shows sociological influences to be a key driver of all antecedent variables, and the most powerful determinant of the relationship commitment.